Contribution of Sports Goods Industry towards Economic Growth of Pakistan - Zafar, Fareeha; Nawaz, Ijaz; Aqib, Muhammad; Shahzad, Nabeel; Yasir, Muhammad (Advances in Social Sciences Research Journal, 2017)
The research focuses on the prevailing issues and challenges faced by sports goods industry in Pakistan. The share of Pakistan sports goods in total exports of Pakistan is 1.51% (2015-16) with football as major export product having 43% share of total sports goods exported in 2012-13 and major export of Pakistan sports goods are to Europe. This study is an attempt to analyze the contribution of sports goods industry in economic growth of Pakistan. This paper depicts importance of sports goods industry for Pakistan. SWOT analysis of Pakistan sports goods industry is presented along statistical values. The results will facilitate sports good industry of Pakistan which exceeds its annual export income of USD 338 million and Sports sectors engaged 200,000 of work force. In addition to this, the paper also presents possible future directions to address aforementioned issues.